The prevalence and associated factors of epilepsy in children in Calicut District, Kerala, India - RJ Hackett L Hackett and P Bhakta (Acta Psdiatr 86: 1257-60. 1997, 1997)
To determine the prevalence of epilepsy and its association with indices of malnutrition, infection and perinatal complications in children in Calicut District, Kerala, India, a door-to-door two-stage survey was conducted in two local government districts. Among the random sample of 1172 children aged 8-lZ y, 26 conformed to the definition of epilepsy giving a 5-y period prevalence of 22.2/1000. A history of perinatal complications, low BMI and recent physical symptoms were independently associated with active epilepsy. The results suggest epilepsy is highly prevalent in this population of children and that further research is needed into its cause